2018
DOI: 10.1111/jch.13144
|View full text |Cite
|
Sign up to set email alerts
|

Resistant hypertension: a therapeutic challenge

Abstract: In 2008, the American Heart Association published resistant hypertension (RH) guidelines.1 Since that year, there has been a lot of research regarding the relevance of making a proper diagnosis and choosing the best treatment. In recent years, there has been an increasing interest in RH because uncontrolled RH is a pathological condition with a poor prognosis.In this regard, it is important to follow steps with the purpose of ruling out pseudoresistant hypertension and then excluding secondary causes. Suboptim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…An estimated 10-30% of hypertensive patients are resistant to treatment defined as uncontrolled blood pressure (BP) with the use of ≥3 medications, including a diuretic [4][5][6][7][8][9][10]. A large number of studies have demonstrated that patients with resistant hypertension compared with patients with controlled hypertension have significantly a higher rate of target organ damage; increased cardiovascular risk, including coronary heart disease, chronic kidney disease, congestive heart failure, and stroke; and a significantly poorer prognosis than those of nonresistant hypertensive patients [3,11].…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 10-30% of hypertensive patients are resistant to treatment defined as uncontrolled blood pressure (BP) with the use of ≥3 medications, including a diuretic [4][5][6][7][8][9][10]. A large number of studies have demonstrated that patients with resistant hypertension compared with patients with controlled hypertension have significantly a higher rate of target organ damage; increased cardiovascular risk, including coronary heart disease, chronic kidney disease, congestive heart failure, and stroke; and a significantly poorer prognosis than those of nonresistant hypertensive patients [3,11].…”
Section: Introductionmentioning
confidence: 99%